(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
The right of members of the public to access information held by public institutions is the fundamental prerequisite for the enthronement of good governance, advancement of human right and consolidation of democratic norms and practice. Democracy depends on open government and the opportunity for people to participate actively, but this cannot effectively and meaningfully take place until the right of citizens, their inalienable rights are guaranteed. It is in the light of the above that this paper examined the freedom of information Act (FOIA) as a tool for the protection and advancement of democracy and human right in Nigeria. The paper critically explores the act to unravel the expected benefits on the right of Nigerians and appraised whether it has impacted positively or negatively on them. The challenges in aiding the advancement of human right in Nigeria and the prospect of overcoming all the hiccups lies with the holistic implementation of the Act to the letter. The paper concludes that ensuring that having access to all the information contend in the Act is the inalienable right of Nigerians and that anything on the contrary constitute a flagrant abuse of the fundamental human right of Nigerians no matter their status in the society.